BIMBINGAN TEKNIS PERENCANAAN TANDON AIR BAWAH TANAH DI SMP NEGERI 22 KOTA MADYA MALANG - Dandung Novianto; Armin Naibaho; Udi Subagio; Gerard Appono; Burhamtoro Burhamtoro (Jurnal Pengabdian kepada Masyarakat, 2021)
With the vision of "Realizing Students Who Are Excellent in Achievement, Skilled, Praised in Character and Cultured in an Environment Based on Faith and Faith" SMP Negeri 22 Malang is located in the eastern area of Malang City, bordering the Malang Regency area, precisely in the hilly area of Villa Gunung Buring, Kelurahan Cemoro, the enclosure of Kedungkandang District, Malang City. This school was founded on October 20, 1999, with a land area of 5,597 m2 with a total area of 2,160 m2 consisting of 36 rooms, the number of study groups is 20 classes, each 6-7 study groups, the total number of students is 610 people and is supported by 35 educators. person. As we know above, with a large enough number of teachers, employees and students, it needs quite a lot of clean water. Whereas the water source at the school is obtained from the distribution of water from the housing whose discharge is very small, so it requires a water reservoir to accommodate water, currently the school only has a water reservoir above with a small volume capacity with a small pressure so that the water is unable to meet even though it has been assisted by a pump due to small water discharge.For this reason, the school has a plan to make an underground water reservoir with the aim of storing water which is then raised to the upper reservoir with the help of a pump, that the water reservoir planning is carried by the ground.